2003
DOI: 10.4049/jimmunol.170.12.6099
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent Antigens Stabilize B Cell Antigen Receptor Surface Signaling Microdomains

Abstract: The B cell Ag receptor (BCR) can distinguish subtle differences in Ag structure and trigger differential responses. In this study, we analyzed the effects of Ag valency on the signaling and Ag-targeting functions of the BCR. Although both paucivalent and polyvalent Ags induced the redistribution of the surface BCR into polarized caps, polyvalent Ag-induced BCR caps persisted. Ganglioside GM1, a lipid raft marker, and tyrosine-phosphorylated proteins, but not CD45 and transferrin receptor, were concentrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 41 publications
5
49
0
Order By: Relevance
“…This discrepancy may reflect the different ligands used to cross-link the BCR. Our study used bona fide Ag, whereas the previous study used polyvalent cross-linkers, such as F(abЈ) 2 of anti-, which have been reported to slow the rate of BCR endocytosis (37). Importantly, our data are consistent with studies showing that BCR mutants lacking the ability to transduce signals remain competent to internalize receptors (28,38,39).…”
Section: Discussionsupporting
confidence: 86%
“…This discrepancy may reflect the different ligands used to cross-link the BCR. Our study used bona fide Ag, whereas the previous study used polyvalent cross-linkers, such as F(abЈ) 2 of anti-, which have been reported to slow the rate of BCR endocytosis (37). Importantly, our data are consistent with studies showing that BCR mutants lacking the ability to transduce signals remain competent to internalize receptors (28,38,39).…”
Section: Discussionsupporting
confidence: 86%
“…The results of previous studies using anti-IgM Abs of varying valencies (29,30) are consistent with our results using multivalent Ag. Extensive cross-linking of the BCR by multivalent Ags induces the association of the BCR with detergent-insoluble lipid rafts (31) that are associated with long-term stable activation of tyrosine phosphorylation (32). The ability of multivalent Ags to establish more stable signaling domains is likely to be responsible for the quantitative boost in up-regulation of markers associated with B cell activation upon stimulation with multivalent HEL on VLPs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study and the work described above (14) highlight distinct pathways of Ab production to polysaccharides and LOS. Polysaccharide Ags contain repetitive carbohydrate epitopes that allow physical cross-linking of specific BCRs in lipid rafts (24). Further, surface CD1d molecules expressed on B cells, especially on CD1d high marginal zone B cells, may comigrate in rafts and transmit an activation signal via their cytoplasmic tail tyrosinecontaining motif, as suggested for CD1d ϩ intestinal epithelial cells (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Further, surface CD1d molecules expressed on B cells, especially on CD1d high marginal zone B cells, may comigrate in rafts and transmit an activation signal via their cytoplasmic tail tyrosinecontaining motif, as suggested for CD1d ϩ intestinal epithelial cells (25,26). In contrast, LOS, which is devoid of repetitive carbohydrate epitopes, may not be efficient in stabilizing lipid rafts (24), but their lipid A structure can transmit supporting signals for IgG responses directed against the sugar chain epitopes of LOS.…”
Section: Discussionmentioning
confidence: 99%